Development and Evaluation of Antimicrobial Edible Films Based on Whey Protein Isolate and Incorporated with Tarragon Essential Oil - Maria-Ioana Socaciu; Melinda Fogarasi; Andersina Simina Podar; Vlad Mureșan; Sonia Ancuța Socaci; Dan Cristian Vodnar; Cristina Anamaria Semeniuc (Biology and Life Sciences Forum, 2021)
The effects of heat treatment and the addition of tarragon essential oil on physical and mechanical properties of films prepared with 5% whey-protein isolate (WPI) and 5% glycerol were investigated in this study. Heat-treatment of the film-forming solution caused increases in thickness, moisture content, swelling degree, water vapor permeability (WVP), b*-value, ΔE*-value, transmittance values in the 200–300 nm region, transparency, and puncture resistance of the film, but decreases in water solubility, L*-value, a*-value, transmittance values in the 350–800 nm region, and puncture deformation. When incorporated with tarragon essential oil, heat-treated films have the potential to be used as antimicrobial food packaging. The addition of tarragon essential oil in film-forming solution caused increases in moisture content, solubility in water, WVP, a*-value, b*-value, ΔE*-value, and transparency of the film, and decreases in L*-value, and transmittance values in the range of 600–800 nm. It also caused variations in swelling degree, transmittance values in the range of 300–550 nm, puncture resistance, and puncture deformation. Nevertheless, different tendencies were noticed in UNT and HT films in terms of transparency, light transmittance, puncture resistance, and puncture deformation. Based on these findings, HT films show improved physical and mechanical properties; therefore, they are more suitable for food-packaging applications.